2019
DOI: 10.1038/s41467-019-12380-6
|View full text |Cite
|
Sign up to set email alerts
|

Tree height explains mortality risk during an intense drought

Abstract: Forest mortality is accelerating due to climate change and the largest trees may be at the greatest risk, threatening critical ecological, economic, and social benefits. Here, we combine high-resolution airborne LiDAR and optical data to track tree-level mortality rates for ~2 million trees in California over 8 years, showing that tree height is the strongest predictor of mortality during extreme drought. Large trees die at twice the rate of small trees and environmental gradients of temperature, water, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
230
6
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 254 publications
(256 citation statements)
references
References 38 publications
17
230
6
3
Order By: Relevance
“…, Stovall et al. ) and increasingly unsuitable climate conditions for establishment (Andrus et al. ), the capacity for P. engelmannii to produce higher abundances of cones at smaller sizes and younger ages than A. lasiocarpa in open‐canopy forests implies that P. engelmannii seed availability may be less limiting than A. lasiocarpa for future seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
“…, Stovall et al. ) and increasingly unsuitable climate conditions for establishment (Andrus et al. ), the capacity for P. engelmannii to produce higher abundances of cones at smaller sizes and younger ages than A. lasiocarpa in open‐canopy forests implies that P. engelmannii seed availability may be less limiting than A. lasiocarpa for future seedling establishment.…”
Section: Discussionmentioning
confidence: 99%
“…For example Trugman et al (2018) showed multiple drought-related phenomena could be reproduced by a simulation model that incorporated drought-induced loss of sapwood conducting area. In particular, their model could simulate drought legacies in addition to greater mortality of larger or older trees during drought (Stovall et al 2019), and for multiple years after drought (e.g. Bigler et al 2007), consistent with Darcy's law (McDowell & Allen 2015).…”
Section: What Are the Underlying Mechanisms?mentioning
confidence: 99%
“…For example, Johnson et al [54] reported research conducted by Rehfeldt [55] that showed genetic differences of Douglas-fir were identified at elevational differences larger than 200 m, whereas genetic differences in ponderosa pine did not occur until 450 m. A genetic difference between two trees of the same species may indicate that one individual tree is not perfectly tuned for a given site; while changes in climatic conditions associated with these elevation ranges are expected to affect the growth characteristics of individual trees with genetic differences [56], the magnitude of climatic change before mortality occurs remains unknown. Additionally, trees may respond differently to changes in climate within a species based on their size and age [57,58], such as through drought-induced mortality caused by carbon starvation or hydraulic failure [59], which the dClim rule does not consider. This study highlighted the effect of the dClim rule, and Climate-FVS users should consider varying the dClim values to determine the effect on their response variables.…”
Section: Carbon Trendsmentioning
confidence: 99%